Konsekuensi Keuangan dan Hukum atas Pelanggaran Hak Cipta dalam Penampilan Publik: Studi Kasus Penyelesaian Sengketa Royalti Musik pada Mie Gacoan Bali - Miftahur Rizki (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The copyright infringement of public appearances at Mie Gacoan Bali Outlet reflects the weak legal awareness of the use of copyrighted works for commercial purposes without permission. The act of playing songs without paying royalties has legal consequences for the company, in accordance with the provisions of Law No. 28 of 2014 concerning Copyright. This research aims to analyze the qualifications of violations that ensnare the company's directors and the form of dispute resolution applied. The method used is normative legal research with a legislative approach and related case studies through qualitative analysis. The results of the study show that the royalty payment obligation of Rp2,264,520,000.00 is calculated based on the Decree of the Minister of Law and Human Rights Number HKI.2.OT.03.01-02 of 2016, with a rate of Rp120,000 per seat per year. Disputes are resolved through a royalty payment mechanism as a form of fulfillment of the economic rights of the creator. This study concludes that strengthening legal understanding, optimizing the implementation of regulations, and improving education and socialization are the keys to creating compliance with copyright protection and encouraging the realization of a fair, ethical, and sustainable music industry ecosystem in Indonesia.